Reflecting upon child protection – the professional doctorate journey. Issue 2 (13th May 2014) - Kettle, Martin
Abstract : Purpose: – This paper draws on a recently completed professional doctorate thesis. The purpose of this paper is to explore how the research process mirrors the area being researched, and underscores the importance of the ability to tolerate ambiguity, in both the research process and in working to protect children. Design/methodology/approach: – The doctorate used a constructivist grounded theory approach, and drew on 22 in-depth interviews with social workers and a sample of 20 serious case reviews. Central to the research process were issues of reflexivity and positionality, which were both crucial to the area under exploration. Findings: – Central to the thesis on which this paper draws, and the professional doctorate is the notion of balance. Social workers and researchers have to negotiate both getting close to and achieving distance from, the subject of enquiry. Seeking and maintaining balance requires managing a number of dimensions, and the negotiation of ambiguity. Originality/value: – This paper explores the complexity of "working the hyphen" of insider-outsider research, and argues that, as in child protection practice, insider-outsider research requires the adoption of strategies to both get close to, and achieve distance from, the subject of enquiry.